Comments on Kevin Stenson's 'governing the Local: Sovereignty, Social Governance and Community Safety' - Wendy Larner (Social Work and Society)
It is a challenging time to be a social scientist. Many of the concepts and categories we took for granted have been revealed as temporally and geographically specific. It is now widely accepted that the nation-state is no longer the sole container for economic, political and social processes, if indeed it ever was. This is where Kevin Stenson begins his paper. He traces the re-ordering of both state and nation, highlighting recent discussions about the unbundling and rescaling of the state and outlining how increasing ethnic and cultural diversity challenge homogeneous conceptions of the nation. In Stenson's account these are largely empirical processes that are the basis for the important questions he raises about changing understandings of publics and social order, and their implications for the local governance of community safety. He contrasts two alternative positions; the "˜universal human rights position' which refuses to privilege the interests of majority populations, and a more 'communitarian and nationalistic position' which he argues is most likely to be deployed by right wing politicians and interests groups. Drawing from extensive research in the Thames Valley region of the United Kingdom, he shows how these two understandings have both shaped the local policy response to crime and disorder.